What does it take for organizations to change themselves? The influences on the internal dynamics of organizational routines undergoing planned change - Murray-Webster, Ruth (Cranfield University, 2014)
Accomplishing desired benefits from investments in planned change is problematical for organizations, their leaders and the change agents charged with delivery. This is despite a well-developed literature, replete with advice on how change should be achieved. Examination of this literature shows the primary focus on change agents and their practices. This research widens the focus by observing the influence of change agents, change recipients and line managers on organizational routines undergoing planned change. It examines the interplay between stability and change in organizational routines, adopting a social practice perspective, and the routine intended to change as the unit of analysis (Feldman and Pentland, 2003, 2005). The research builds on claims that to understand the patterns of action within routines requires the internal dynamics – the claimed duality between ostensive (in principle) and performative (in practice) aspects - to be examined. A research method to operationalize the study of this claimed duality was devised following the principles of Strong Structuration (Stones, 2005). This method enabled a unique conceptualization of the study of routine dynamics, focused on planned change from the perspective of multiple, interdependent actors. Two cases of change agents following the advice in the planned change literature were explored. In one case, stability of the routine persisted when change was intended. In the other, change was relatively easy to achieve irrespective of change agent actions. The primary contribution is the demonstration of how the attitudes to change of change recipients, line managers and change agents influence the internal dynamics of routines undergoing planned change. Other contributions pertain to the method of ‘unpacking’ organizational routines and its potential for shaping future practice. This research does not offer new ‘normative’ advice but instead sensitizes planned change practitioners to the level of analysis they need to carry out to ensure that their interventions are suitably designed.
Keywords: Planned change; organizational routines; Strong Structuration; social practice theory; change agents; change recipients; case studies